Biological production of hydrogen and acetone- butanol-ethanol from sugarcane bagasse and rice straw using co-culture of Enterobacter aerogenes and Clostridium acetobutylicum. (November 2020) - Tondro, Hadiseh; Musivand, Sogand; Zilouei, Hamid; Bazarganipour, Mehdi; Zargoosh, Kiomars
Abstract: Production of hydrogen and acetone-butanol-ethanol (ABE) from hydrolysates of sugarcane bagasse (SCB) and rice-straw (RS) was carried out via dark fermentation using co-culture of Enterobacter aerogenes and Clostridium acetobutylicum . The best improvement in the yield of hydrogen and total ABE production were observed for alkaline pretreated RS at 100 °C for 60 min obtained from the highest total reducing sugars concentration of 40.7 g L −1 after the enzymatic hydrolysis. The hydrolysates of alkaline pretreated samples at 100 °C were efficiently converted to H2 by co-culture of Enterobacter aerogenes and Clostridium acetobutylicum with the highest hydrogen yield of 136.3 and 149.9 mL H2 g −1 -VS of SCB and RS, representing 3.4 and 1.5-fold enhancement in the hydrogen production yield over that obtained from the pure cultures of Enterobacter aerogenes and Clostridium acetobutylicum, respectively. Mass balance and energy generation analysis indicate that the highest specific ABE and total energy production yields per gram untreated feedstock reached 0.12 g ABE and 5.5 kJ for SCB and 0.08 g ABE and 6.6 kJ for RS. Graphical abstract: Image 1 Highlights: Integrating production of H2 /ABE fom sugarcane-bagasse and rice-straw was studied. dark fermentation using co-culture of E. aerogenes and C. acetobutylicum was used. 3.4-fold improvement in H2 yield was observed in co-culture vs. pure cultures. From 1 kg of sugarcane bagasse, 136.3 L H2 and 115 g ABE were produced. From 1 kg of rice straw, 149.9 L H2 and 86 g ABE were produced.